Association of Myeloma in Patients of Chronic Kidney Disease; A Single Centered Study - Farzana Adnan Sheikh; Syed Tajammul Ali; Sidra Rashid; Mehwish Qamar; Khadijah Abid (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the frequency along with socio-demographic factors and clinical features of myeloma in patients with chronic kidney disease (CKD) presenting at a tertiary care hospital in Karachi, Pakistan.